Investigation of metal cored arc welded FCA (Fatigue Crack Arrester) steel in terms of microstructure, toughness and tensile properties - Kazasidis, Marios (Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2018)
The present thesis focuses on the investigation of the microstructural characteristics and the mechanical properties of the newly-developed AH-40 FCA (Fatigue Crack Arrester) steel when welded with the Metal Cored Arc Welding technique in a butt joint configuration. At first stage, bead on plate trials were conducted on the surface of AH-40 FCA steel plates 13 mm thick and were subsequently investigated as a preliminary study of the multipass welding. Their operational welding conditions were determined by means of welding heat input. More specifically, five values of heat input levels were used i.e. 0.5, 1.0, 1.5, 2.0, 2.5 kJ/mm. The geometric parameters of the beads and their microhardness distributions were examined leading to the qualification of heat inputs at 1.0 and 1.5 kJ/mm as optimum for bead on plate welding. The multipass welds were implemented with the aforementioned heat input levels, while the optimization of the process was accomplished with regard to the microstructure and the tensile properties of the welds. For this purpose, the respective standards ISO 17639 and ISO 4136 were followed. The microstructural characterization was performed with optical microscopy, scanning electron microscopy with energy-dispersive X-ray spectroscopy, and microhardness testing with the Vickers method. In addition, the transverse tensile test was selected not only for the estimation of the tensile properties of the welds, but also for the determination of the most vulnerable area of the weld. The results correlated the welding operational conditions with the microstructure and the tensile performance of the welds. The established optimization criteria comprise parameters such as the width of the Heat Affected Zone, the homogeneity of the microstructure, the microstructural constituents, the grain size, the microhardness distribution, the strength and the ductility of the weldments. The obtained results qualified the weldment with heat input level at 1.0 kJ/mm as the optimum with regard to the combination of microstructure, strength, and ductility. The subsequent steps of the thesis include additional experimentation with regard to the optimum weldment, focusing on its most vulnerable region and more specifically its weld metal. The welding-induced residual stress distribution was measured on the weldments surface. Moreover, the population and size of non-metallic inclusions in the weld metal microstructure was investigated. The latter parameters alongside with the microstructural characteristics examined during the optimization step were correlated with the toughness properties of the AH-40 FCA optimum weld. More specifically, the impact toughness was evaluated with the execution of Charpy test, while fracture toughness with the Crack Tip Opening Displacement test (CTOD or fracture toughness testing). The European standards ISO 148 and ISO 12135 were followed respectively. The experiments led to the quantification of the toughness parameters comparatively for the weld metal and the base metal by testing appropriate notched specimens extracted from both regions. More specifically, the absorbed Charpy energy, the Lateral Expansion (LE), and the Percentage of Shear Fracture (PSF), were recorded as functions of the test temperature, while the crack tip opening displacement values were estimated at room temperature. As far as the analytical model is concerned, the necessity for its construction emanated during the optimization step, where the effect of the welding parameters on the required number of beads for the implementation of a multipass welding was observed in practice. The model was divided into two analytical methods entitled “PRA” and “PNB”. Both are governed by their two respective iv functions which were mathematically proven and established by following the fundamental principles of welding technology and ISO 9692 standard. PRA (Prediction of the Reinforcement Area) calculates the theoretical reinforcement area in a Stringer bead (for this reason it is designated as PRA-S). The construction of PNB (Prediction of the Number of Beads) method was based on the PRA, aiming at the estimation of the number of beads in multipass welding with stringer beads and preselected welding conditions. The input/independent variables of the model were the welding current/wire feed rate, and the welding travel speed as well as the electrode type (solid, flux cored, metal cored), the electrode diameter, and the thickness of the specimens to be welded. The parametric analysis provides solutions to productivity issues as it can be applied for the calculation of the required net time of multipass welding procedures. In addition, it can be used as a standardized technique for the quality control of the flow production of welded structures in assembly lines of both the construction and the shipbuilding industry. The results of the PhD thesis shed light on the feasibility of AH-40 FCA steel welding with metal cored wire. The assessment of the weldments properties with regard to their microstructure, and their response to mechanical loading was implemented. These results were correlated with productivity issues. Consequently, the present study enriched the existing literature and extended it into novel areas of interest. Keywords: AH-